Observational and Simulative Study of a Local Severe Precipitation Event Caused by a Cold Vortex over Northeast China - Ying Liu; Zhaoming Liang; Yupeng Li (Advances in Meteorology)
A severe precipitation event around Changchun-Yongji in Jilin Province, China, during 27–29 July 2010 was investigated, with a focus on the comparative analysis of 2 heavy precipitation episodes. This was done using NCEP gridded analysis data, intensive surface observations, and radar and satellite measurements. The Weather Research and Forecast (WRF) model was used to simulate the precipitation process and explore mechanisms for the development and dissipation of the severe precipitation event. Precipitation in the first stage was induced by the convergence of northwesterly winds at the rear of the cold vortex and southwesterly winds that reached the rainfall region. However, in the second stage, because of the blockage caused by Changbai Mountain, winds at the bottom of the cold vortex turned from the northwest to the northeast. These winds strongly converged with the southwesterly winds and continuously triggered new convective clouds, which were associated with cold centers at the surface. The intensity of the cold center modulated the strength of the convective cells and resulting precipitation quantity. Furthermore, the local terrain features and direction of the motion of the airflows were critical in triggering convection.